2019
DOI: 10.3390/w12010052
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Peak Flow Distribution for Bridge Collapse Sites

Abstract: Bridge collapse risk can be evaluated more rigorously if the hydrologic characteristics of bridge collapse sites are demystified, particularly for peak flows. In this study, forty-two bridge collapse sites were analyzed to find any trend in the peak flows. Flood frequency and other statistical analyses were used to derive peak flow distribution parameters, identify trends linked to flood magnitude and flood behavior (how extreme), quantify the return periods of peak flows, and compare different approaches of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…However, not infrequently it is observed that bridges collapse under floods having very low return periods. In general, the floods that cause failure due to scour are considerably scattered, in a range between 1 and more than 1000 years [9,169,170]; therefore, scour accumulation may have an active role in those failures occurring for floods with low return periods [144]. Figure 8 describes the empirical relationship between the return periods (T R ) of flood events producing bridge collapse and the bridge age, resulting from a study performing the historical analysis of bridge collapses in the U.S.A. [144].…”
Section: Type Of Routementioning
confidence: 99%
“…However, not infrequently it is observed that bridges collapse under floods having very low return periods. In general, the floods that cause failure due to scour are considerably scattered, in a range between 1 and more than 1000 years [9,169,170]; therefore, scour accumulation may have an active role in those failures occurring for floods with low return periods [144]. Figure 8 describes the empirical relationship between the return periods (T R ) of flood events producing bridge collapse and the bridge age, resulting from a study performing the historical analysis of bridge collapses in the U.S.A. [144].…”
Section: Type Of Routementioning
confidence: 99%
“…Physiographic settings, such as Appalachian Highland, Central Lowland, and Coastal Plain, do possess high erodible beds and/or banks along with other disturbances such as debris jams, backwaters from Bays and/or intensive human interventions (Johnson, 2006; Simon & Rinaldi, 2000). Under such circumstances, the river sections will not be resilient to lower flows as would have been expected, and therefore collapse risk even at low flows (or flows with lower return periods) can be expected (Ashraf & Flint, 2020, 2021). Since all these collapse‐inducing conditions can manifest in a specific trend of hydraulic geometry, as derived for the study sites with limited human interference, certain trends in AHG can be arguably used as a criterion for risk analysis along with certain flow characteristics, such as low return period of heavy tail flows.…”
Section: Discussionmentioning
confidence: 99%
“…An α-value is used for determining the significance of Kendall's τ (Villarini et al, 2009). To check the behavior of the bank full flow, the shape parameter value of the flow distribution is extracted (Ashraf & Flint, 2020) increase more than the exponential order as compared to the low flows in the light tail. To check whether the bank full flow falls within the heavy or light tail category for a heavy tail flow distribution, this study employs the Jiang classification scheme (Jiang, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow conditions vary in different regions, making flooding a major cause of damage to highway and railway bridges. Bridge collapses due to floods are not uncommon, and frequent flood disasters, inherent deficiencies in foundation design, and human-induced changes in riverbeds are the primary culprits [57][58][59][60][61]. Data maintained by The New York State Department of Transportation show that, between 1992 and 2014, hydraulic-induced failure caused 55.4% of the 428 bridge collapses in their database [62], and a historical analysis of hydraulic bridge collapses is performed to check the relationship between bridge collapses and flood frequency or intensity [63].…”
Section: External Natural Factorsmentioning
confidence: 99%